2018
DOI: 10.1007/s00436-018-5965-9
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection: the outcome of Plasmodium infection differs according to the time of pre-existing helminth infection

Abstract: Although helminth-Plasmodium coinfections are common in tropical regions, the implications of this co-existence for the host immune response are poorly understood. In order to understand the effect of helminth infection at different times of coinfection on the immune response against Plasmodium infection, BALB/c mice were intraperitoneally infected with Taenia crassiceps (Tc). At 2 (Tc2) or 8 (Tc8) weeks post-infection, mice were intravenously infected with 1 × 10 Plasmodium yoelii (Py) 17XL-parasitized red bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Also, participants were not followed to determine if any of them progressed to febrile disease and to assess trends in the cytokine profile during asymptomatic infection and disease onset in the same individuals. Also, the presence of other infectious diseases such as helminth co-infections which were unaccounted for may account for some of the differences in the cytokine profile since they are common in children of school-going age (Brooker et al, 2007;Salazar-Castañón et al, 2018). Nevertheless, we have been able to show that asymptomatic malaria infections are characterized by a concomitant upregulation of both proand anti-inflammatory cytokines, specifically TNF-α, IFN-γ, IL-6, IL-17A, and IL-4 as assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, participants were not followed to determine if any of them progressed to febrile disease and to assess trends in the cytokine profile during asymptomatic infection and disease onset in the same individuals. Also, the presence of other infectious diseases such as helminth co-infections which were unaccounted for may account for some of the differences in the cytokine profile since they are common in children of school-going age (Brooker et al, 2007;Salazar-Castañón et al, 2018). Nevertheless, we have been able to show that asymptomatic malaria infections are characterized by a concomitant upregulation of both proand anti-inflammatory cytokines, specifically TNF-α, IFN-γ, IL-6, IL-17A, and IL-4 as assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…crassiceps and P . yoelli survived longer than mice infected with the malaria parasite only, which the authors correlated with a reduction in IFN-γ levels [65]. These studies point to a crucial role for IFN-γ in modulating a secondary Plasmodium infection.…”
Section: Discussionmentioning
confidence: 96%
“…Parasite MIF can participate in regulating the host's immune response and is an important medium for the host to resist infection and promote immune cell stress responses 1,21,22 . Several studies have reported that parasite MIF encodes 114–146 amino acids and the relative molecular mass is 11–16.4 kDa 23 . Many studies have shown that the MIF trimer is the biologically active form.…”
Section: Discussionmentioning
confidence: 99%